'Bio-bordering' processes in the EU: de-bordering and re-bordering along transnational systems of biometric database technologies. (3rd March 2020) - Amelung, Nina; Machado, Helena
Biometric data is increasingly flowing across borders in order to limit and control the mobility of selected people not only for migration control but also for crime control. The promise is that while data is mobilised, those declared outlaws will be immobilised. In this article, we discuss reverse patterns of bordering and ordering practices linked to large-scale transnational biometric database infrastructures. We introduce the concept of bio-bordering, using it to capture how the territorial foundations of national state autonomy are partially reclaimed and, at the same time, partially purposefully suspended when establishing biometric data exchange. The case of the Prüm system, the mandatory exchange of forensic DNA data amongst the EU member states, serves to portray instances of overcoming and enforcing bio-borders for data flows. Firstly, we explore the different logics of creating permeable bio-borders at work at the EU level which derive from EU attempts of integrating legal, scientific, technical and organisational dimensions. Secondly, we take the Portuguese case as an illustrative example of how latently reinforcing bio-borders counters the ambition of expansive data exchange.